APPLICATION OF CRIMINAL SANCTIONS AGAINST PERPETRATORS OF PSYCHOLOGICAL DOMESTIC VIOLENCE IN HOUSEHOLDS - tri, yesi; Dona Raisa Monica; Firganefi (Faculty of Law-Universitas Bandar Lampung, 2024)
Domestic Violence is a complex issue influenced by various factors, including a lack of awareness and understanding of psychological violence as a legal violation. Although Law Number 23 of 2004 on the Elimination of Domestic Violence (PKDRT) regulates forms of violence such as physical, psychological, sexual, and economic neglect, its enforcement still faces numerous challenges. Criminal sanctions against perpetrators of psychological violence, such as imprisonment or fines, often fail to provide a sufficient deterrent effect due to multiple inhibiting factors. This study employs a normative juridical method with a literature review approach to understand the application of criminal sanctions against perpetrators of domestic violence. The results indicate that the main challenges in law enforcement include weak legislation, limited understanding among law enforcement officers, inadequate support facilities, and low public awareness of victims rights. Additionally, patriarchal cultural factors, social stigma, and the perception that domestic violence is a private matter exacerbate the situation. The lack of public education on victims' rights and legal procedures further complicates the law enforcement process. Data show that psychological violence is one of the most frequently reported forms of domestic violence, yet its handling remains suboptimal. Legal reform, improved capacity of law enforcement, and better support services for victims are crucial to ensuring effective protection and recovery. Furthermore, public education and changing mindsets, along with addressing gender-biased cultural norms, are essential to overcoming domestic violence issues.